P159 On the road: delivering sexual health services to vulnerable populations in hard-to-reach areas. (23rd May 2012) - McMillan, S; Scott, P; Ormerod, D; Jones, R
Abstract : Background: Studies show a correlation between poor general and sexual ill health. These health inequalities are not evenly distributed within the population. Hammersmith & Fulham (H&F) houses some of the most deprived areas in England, many of which have high rates of ill health. Barriers to successful community healthcare engagement are manifold and encompass access, stigma and social issues. Aims/Objectives: In order to tackle these barriers, increase engagement and subsequent uptake of screening we deliver wellperson screens, incorporating sexual health checks, in a purpose built healthbus targeting the most economically challenged areas of H&F. The service was designed to normalise sexual health screening in the context of a routine "check-up." Method: In 2011, 15 clinics were provided. Data were collected pertaining to gender, ethnicity, screening/service provision, well-being parameters, referrals and follow-up. Results: 243 patients attended the health bus, 145 were male. Almost half (46.9%) accepted sexual health screening leading to the identification of HIV (one), Syphilis (one) and Chlamydia (five). Wellperson checks led to 59 referrals to allied services, pertaining to 52 individuals. One third (19) of those referrals were to level three sexual health services, just under two-thirds (37) were referred to their GP (25 for hypertension, one for glucosuria and 11 for other medical reasons) and three were referred to smoking cessation services. Discussion/Conclusion: Linking sexual health with general well-being checks has shown to be an acceptable way to increase screening uptake in our local community. The clinic has also highlighted the extent of ill health in H&F, continued health promotion via innovative strategies such as the healthbus may help to tackle these health inequalities.